The Beauty of Luang Poo Yai Chai Mongkol (Buddha’s Image) According to the View of Relativism - mahitthik, Phra Aon; Thongpan, Suwin (Dhammathas Academic Journal, 2019)
The objective of this academic article was to study the beauty of Luang Poo Yai Chai Mongkol according to the view of relativism. Luang Poo Chai Mongkol is the evil-defeated Buddha’s statue. If we mentioned the beauty of the Buddha’s statues, there will be a variety of views. In this article, it will shows the beauty of Luang Poo Chai Mongkol according to the view of relativism. The beauty of the Buddha’s statue in Relativism’s view is composed of 2 elements. These were: 1. Knowing (internal), and 2. The object is known (External appearance and both must have a relationship to each other and so the beauty will be appears. Therefore, the beauty of Luang Poo Chai Mongkol will be appears when the knower have seen Luang Poo Chai Monkol and known it by eye, such as, The beauty of the face and the body wars full with dignity. The worshipers worshiped and have faith in Luang Poo Chai Mongkol and another beauty is from the environmental context. Luang Phor Yai Chai Mongkol enshrined prominently on the altar in the chapel which was surrounded by beautiful murals. So, Luang Poo Yai Chai Mongkol is the beauty of the Buddha’s statue according to the view of relativism.